2015
DOI: 10.5455/jice.20151030085004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an ethanolic seed extract of Picralima nitida ((Stapf) Th. and H. Durand) on reproductive hormones and its safety for use

Abstract: Background:Picralima nitida seed extract (PNE) has aphrodisiac and contraceptive effect.Aim:To investigate the effect of PNE on reproductive hormones.Materials and Methods:The size and length of the combs of white leghorn day-old chicks treated with testosterone (0.5-1.5 mg/kg), cyproterone (3-30 mg/kg), or PNE (50-500 mg/kg) for 7 days, as well as cyproterone (10, and 30 mg/kg) on PNE-induced, and PNE (50-500 mg/kg) on testosterone-induced comb growth, were measured in the chick comb test. The effect of PNE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…If Zn deficiency occurred, atrophy of seminiferous tubules and spermatogenesis disorder would follow [26]. Some studies showed that the increase in the testosterone content was consistent with good quality voice, strong muscles, and good comb growth [8,[42][43][44]. In addition, the increase in testosterone was also consistent with the reproduction capability, as indicated by mating success [45].…”
Section: Effects Of a Granosa Shell Powder On Testosterone Levelsmentioning
confidence: 99%
“…If Zn deficiency occurred, atrophy of seminiferous tubules and spermatogenesis disorder would follow [26]. Some studies showed that the increase in the testosterone content was consistent with good quality voice, strong muscles, and good comb growth [8,[42][43][44]. In addition, the increase in testosterone was also consistent with the reproduction capability, as indicated by mating success [45].…”
Section: Effects Of a Granosa Shell Powder On Testosterone Levelsmentioning
confidence: 99%
“…The length of comb with Zinc sulfate and NAB groups was shorter compared to the control. However, looking at the details, there was a significant difference from the 4 th week to the 5 th week; this means there is a significant [11], the growth of wattle or comb in male chickens highly depends on the testosterone produced by Leydig cells in the testes. The testosterone produced will be secreted and transported to the comb and will grow.…”
Section: Treatmentmentioning
confidence: 99%
“…After a statistical test was carried out, it could be proven that NAB did not lead to the accelerated growth of wattle size (p-value > 0.05). Otoo et al [7] stated that the growth of wattle or comb in male chickens is highly dependent on the testosterone produced by Leydig cells in the testes. The testosterone produced will be secreted and transported to the comb and will grow.…”
Section: Effect Of Nab Treatment On Wattle Sizementioning
confidence: 99%